Research on Machining Fixture Layout Optimization for Near-Net-Shaped Jet Engine Blade. (November 2019) - Zhang, Kaiyao; Wu, Dongbo; Wang, Jiao
Abstract: The design of machining fixture layout optimization for near-net-shaped jet engine blade is a major problem in the blade processing and manufacturing process. In this paper, the mathematical model of machining fixture layout optimization is established, and the influence of the clamping point position on the machining deformation of the blade-fixture system is analysed. Firstly, the mathematical model of machining fixture layout optimization is established according to the process requirements and clamping characteristics. Secondly, the positioning clamp points of machining fixture is optimized by the combination of finite element analysis (FEA) and genetic algorithm under the optimization target of the minimum value of the maximum deformation of the blade. Finally, cutting experiments are carried out to verify the reliability of the optimal layout fixtures, and the feasibility of the algorithm is verified by comparing with the minimum value obtained by the traditional Monte Carlo statistical method.